Inclusão do Farelo da Mamona Desintoxicada na Alimentação da Tilápia do Nilo (Oreochromis niloticus). - Silva, Viviane de Oliveira (2010)
The aim of this study was to evaluate the performance of Nile tilapia subjected diets with different levels of inclusion of detoxified castor meal (FMD). Was conducted in the Laboratorio de Recursos Aquáticos - LARAq, Department of Fisheries Engineering, Federal University of Ceará. The growth performance of Nile tilapia was evaluated based on weight gain, biomass gain, final biomass, feed conversion, survival, feed consumption and growth rate, hepatosomatic index (HSI), fat index viscerosomático (IGVS ), viability was observed. The physico-chemical parameters of the water for cultivation were performed: pH, dissolved oxygen, conductivity, temperature, saturation, concentration of ammonia, nitrite and ósforo. The tilapia had average initial weight and length of 6.11 ± 0.03 g 71.88 ± 3.44cm. 03 were formed each containing operating systems, tanks 03 and 06 1000L tanks networks 1m ³ with 80 fish each. In a randomized complete causalizado with 06 treatments and 03 replications. 06 were formulated isoenergetic 3000 kcal / kg and 30% CP isonitrogenous differing in the level of inclusion of FMD (0, 12, 24, 36, 48 and 60%). The experimental period was 92 days in a closed system of water circulation. For the physical parameters of the water cultivation no significant difference (p> 0.01). A significant difference (p> 0.01) in the concentration of ammonia and phosphorus between systems. We observed differences in weight gain, average feed intake, gain, biomass, biomass growth rate only average feed conversion was no significant difference p> 0.01. The castor bean meal in the diets did not influence the IHS and IGVS. For economic values, the diet containing 48% of FMD had the lowest with CMR (£ 1.99). The diet of 0% FDM had the highest average cost of feed per kg of live weight diet, and the lowest rate of economic efficiency (47.92) and the 48% diet the highest rate (100). For the HF diet with 48% of FDM and has the lowest cost diet with 0% FDM falls as higher cost (208.69). In carcass composition of the fish worked there was a significant difference (p> 0.01) in moisture and crude protein of fish carcasses at the beginning and end of cultivation. As for the level of fat, showed a significant difference p> 0.01 fish early and fish fed the diet containing 60% of FMD. It was concluded that at up to 12% of FDM zootechnical performance is increased above this percentage is the impairment in water quality and increased carcass ethereal extract of fish and lower protein meat.